The Meaning of Ad-DÄ«n and Its Relevance to Religious Life (Hermeneutical Reading of Muhammad Asad's Interpretation in The Message of the Qur'an) - Qotrunnada, Qotrunnada; Maimun, Muhammad; Nurkholidah, Nurkholidah (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2024)
This paper aims to reveal the meaning of the word ad-dÄ«n according to Muhammad Asad in The Message of the Quran. This paper is the result of qualitative research using Hans-Georg Gadamer's hermeneutic approach. The word ad-dÄ«n is often known in general only to mean religion and refer to Islam. However, the word ad-dÄ«n has a wide variety of meanings and meanings. The result of this study, the word ad-dÄ«n in the Qur'an according to Muhammad Asad means, namely, Law, Faith, Judgment, Obedience, Moral Law, Dependent, Worship, Pay, Under the King's Law, and Religion. Its contemporary relevance, for Asad, is to understand a word in the Qur'an; First, it must pay attention to the meaning of the word as a whole, comprehensively and deeply. This will give birth to a view of the concept in a unified whole, both the doctrinal aspects and the practical implications of religious practice that will give birth to moderate understanding and action. Second, religions have their own truths. In a sense, each shows the nature of obedience, submission, and belief in the oneness of Allah swt in a religious life that is beneficial and sustainable.